A Comprehensive Review of Sulfide Solid-State Electrolytes: Properties, Synthesis, Applications, and Challenges - Bin Man; Yulong Zeng; Qingrui Liu; Yinwen Chen; Xin Li; Wenjing Luo; Zikang Zhang; Changliang He; Min Jie; Sijie Liu (Crystals)
Traditional lithium-ion batteries (LIBs) utilize liquid electrolytes, which pose significant safety risks. To address these concerns and enhance energy density, all-solid-state batteries (ASSBs) have emerged as a safer and more efficient alternative to conventional liquid electrolyte-based systems. ASSBs offer notable advantages, including higher energy density and improved safety, driving growing interest from both industry and academia. A key component in all-solid-state battery (ASSB) development is the solid-state electrolyte (SSE), which plays a crucial role in determining the overall performance and safety of these batteries. Sulfide SSEs are characterized by distinctive attributes, including notably high ionic conductivity and remarkably low interfacial resistance with lithium metal anodes, which renders them particularly advantageous for advancing ASSB technology. This paper systematically examines sulfide-based SSEs, with particular emphasis on their underlying physicochemical properties, structural characteristics, and essential functional attributes relevant to ASSB applications. Additionally, we explore preparation methods for sulfide SSEs and analyze their potential applications in next-generation ASSBs. Considering current challenges (e.g., interfacial instability or air sensitivity) we summarize strategies to address these obstacles, aiming to facilitate their integration into future energy storage systems.